2021
DOI: 10.48550/arxiv.2105.14956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging Mobile Phone Data for Migration Flows

Abstract: Statistics on migration flows are often derived from census data, which suffer from intrinsic limitations, including costs and infrequent sampling. When censuses are used, there is typically a time gap -up to a few years -between the data collection process and the computation and publication of relevant statistics. This gap is a significant drawback for the analysis of a phenomenon that is continuously and rapidly changing. Alternative data sources, such as surveys and field observations, also suffer from rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Telecommunication companies collect information regarding people's exchanges by means of Call Detail Records (CDRs), which contain real-world observations on how, when and with whom a person communicates (Blondel et al, 2015;Luca et al, 2021). A Call Detail Record is a tuple (u o , u i , t, d, A o , A i ) which contains privacyenhanced metadata about the caller u o , the callee u i , the timestamp t of when the call took place and its duration d. A o and A i represent respectively the outgoing and incoming Radio Base Stations (RBSs), namely the antennas that delivered the communication through the network.…”
Section: Call Detail Recordsmentioning
confidence: 99%
“…Telecommunication companies collect information regarding people's exchanges by means of Call Detail Records (CDRs), which contain real-world observations on how, when and with whom a person communicates (Blondel et al, 2015;Luca et al, 2021). A Call Detail Record is a tuple (u o , u i , t, d, A o , A i ) which contains privacyenhanced metadata about the caller u o , the callee u i , the timestamp t of when the call took place and its duration d. A o and A i represent respectively the outgoing and incoming Radio Base Stations (RBSs), namely the antennas that delivered the communication through the network.…”
Section: Call Detail Recordsmentioning
confidence: 99%
“…For example, some experts suggest that uses of cell phone data to help tackle humanitarian crises and infectious diseases in LMICs are very likely to be repurposed to predict, track and prevent unwanted migration. 45,46 Foreign involvement in the African communication technology sector, particularly that of the Chinese government, has also raised questions about function creep and accountability. 47 Chinese companies like Huawei and the Transsion Group have invested heavily in the cell phone infrastructure of SSA.…”
Section: Function Creep and Accountabilitymentioning
confidence: 99%
“…The principle of data migration enables data transfer from one or more storage spaces to the same or different computer system platforms or locations to improve data scalability, accessibility, and portability, as well as reducing the cost of information technology operations in businesses and organizations [12][13][14][15][16]. In recent years, numerous data migrations have been focused on storage [17], application [18], business process [19], DBMS [20,21], and platforms [13,[20][21][22]. Many studies have identified significant concerns in data migration strategies, such as data validation [23], integrity checks, efficient migration techniques [24,25], heterogeneous data migration [26,27], and data migration frameworks for sustainable decision making [28].…”
Section: Introductionmentioning
confidence: 99%